PERAN KEBIJAKAN FISKAL DALAM MENDUKUNG STABILITAS EKONOMI MAKRO - Amanda Mutiara; Imel Santika Siregar; Maysa Chairani; Luthfia Masfa Nur; Yauma Afriyanti; Tasya Nadilla (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to fill several important research gaps in the context of fiscal policy in Indonesia. First, the research will evaluate the effectiveness of fiscal policy in supporting macroeconomic stability, which is a fundamental basis for sustainable economic growth and increasing social welfare. The research method applied in this study is a qualitative approach using the library research method. Fiscal policy in Indonesia during the 2010-2023 period has proven effective in encouraging economic growth and reducing unemployment, but it needs to be balanced with prudent policies to maintain price stability and the state budget deficit.